2-(Methoxycarbonyl)quinolinium tetrachlorido(quinoline-2-carboxylato-kappa N-2,O)stannate(IV) methanol solvate - Vafaee, M.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title salt, (C11H10NO2)[SnCl4(C10H6NO2)]center dot CH3OH, the Sn atom is chelated by the quinolincarboxylate unit and it exists in a distorted octahedral coordination geometry. The cation is linked to the solvent molecule by an N-H center dot center dot center dot O hydrogen bond; the solvent molecule is linked to the anion by an O-H center dot center dot center dot O hydrogen bond.